HARTA DALAM ISLAM (Peran Harta Dalam Pengembangan Aktivitas Bisnis Islami) - Wening Purbatin Palupi (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2013)
These days, in society reality around us of ownership of of estae represent standardization in determining bliss of someone life, estae which abundance indicate that he is child of fortune. So that with assumption, according to economizing writer, enough become a reason why human being of cendrung race to multiply properties estae had, because requirement of human being or human being easiness to same estae of its position with requirement of human life to child and or clan. Estae which abundance on earth, before us, basically represent absolute property of Allah of Swt, as creator and power of universe along with its contents. With understanding, of estae which human being have or master only owning role as proxy Allah of swt, to managing it with management mechanism in charge of as according to rule of the game which have in Allah nash of swt in Al-Quran and also rule which have teaching Rasulullah Muhammad saw, for stock live and life of eternity world.